Effects of Diet on Susceptibility to Azinphosmethyl of the Tufted Apple Bud Moth Platynota Idaeusalis (Lepidoptera: Tortricidae) - Domínguez Gil, Oscar; Mcpheron, Bruce (Boletín del Centro de Investigaciones Biológicas)
We determined the effect of diet on insecticide resistance in two genetically similar strains (one susceptible and one resistant to azinphosmethyl) of the tufted apple bud moth (Platynota idaeusalis). Susceptibility to azinphosmethyl was studied by bioassay of larvae fed a synthetic diet and four different host plant species: apple (Malus domestica), cv Red Yorking; black raspberry (Rubus occidentalis); broad-leaved plantain (Plantago major); and dandelion (Taraxacum officinale). Susceptible-strain larvae fed dandelion were significantly more tolerant to azinphosmethyl than those fed with other diets. Resistant-strain larvae reared on black raspberry were not significantly different from apple-fed larvae, but were more susceptible than those raised on plantain, dandelion, or artificial diet. Analysis of dose-mortality regressions suggests that different mechanisms may be induced by hosts in the susceptible strain, but the resistant strain responds to host chemistry by using different activity levels of the same enzymatic mechanism. Overall effect of host plants on toxicity of azinphosmethyl to P. idaeusalis was significant. To preserve susceptibility of P. idaeusalis to azinphosmethyl, abundance and number of host plants present in orchard ground cover should be taken into account.